Exclusive f1(1285) meson production for energy ranges available at the GSI-FAIR with HADES and PANDA - Lebiedowicz, Piotr; Nachtmann, Otto; Salabura, Piotr; Szczurek, Antoni (Physical review, 2021)
We evaluate the cross section for the pp→ppf1(1285) and p¯p→p¯pf1(1285) reactions at near threshold energies relevant for the HADES and PANDA experiments at GSI-FAIR. We assume that at energies close to the threshold the ωω→f1(1285) and ρ0ρ0→f1(1285) fusion processes are the dominant production mechanisms. The vertex for the VV→f1 coupling is derived from an effective coupling Lagrangian. The gρρf1 coupling constant is extracted from the decay rate of f1(1285)→ρ0γ using the vector-meson-dominance ansatz. We assume gωωf1=gρρf1, equality of these two coupling constants, based on arguments from the naive quark model and vector-meson dominance. The amplitude for the VV→f1 fusion, supplemented by phenomenological vertex form factors for the process, is given. The differential cross sections at energies close to the threshold are calculated. In order to determine the parameters of the model the γp→f1(1285)p reaction is discussed in addition and results are compared with the CLAS data. The possibility of a measurement by HADESGSI is presented and discussed. We perform a Monte Carlo feasibility simulation of the pp→ppf1 reaction for √s=3.46 GeV with the f1 decaying into the π+π−π+π− (not shown explicitly) and π+π−η(→π+π−π0) final states using the PLUTO event generator. The latter f1 decay is especially promising as a peak in the π+π−η mass distribution should be observable by HADES.